Pengaruh Kompensasi Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Intervening ( Studi Empiris Pada Pt. Iskandar Indah Printing Textile ) - Andriana, Vina; , Nur Achmad, S.E., M.Si (2017)
The purpose of this study was to analyze the effect of compensation to employee performance and analyze the effect of compensation to employee performance and motivation as an intervening variable. This type of research is a uantitative study with statistical analysis through survey research. The study population is not permanent employees at PT. Iskandar Indah Printing Textile some 130 people. A sample of 56 people by using simple random sampling method, with the formula Slovin. Data were analyzed using quality test instrument, the classical assumption test and test potheses. The results showed: (1) Compensation positive and significant effect on the performance of temporary employees at PT. Iskandar Indah Printing Surakarta. This is proved by obtaining the regression coefficient (b1) positive at 0.663, and supported the value t = 6,049, and 0,000 sign. (2) Compensation direct influence on employee performance is not fixed at PT. Iskandar Indah Printing Surakarta through motivation. This is proved by obtaining the regression coefficient (b2) the positive value of 0.432, the valuet = 3.009 and 0.003sig.